Comprehensive evaluation of molecular, clinical, and hematological profiles in familial mediterranean fever - Muwafaq Mohsin Thalaj; Khalid N M AL-Kheroo; Muna Abdulbasit Kashmoola (Iraqi Journal of Hematology, 2026)
Abstract: BACKGROUND: Familial Mediterranean fever (FMF) is an autosomal recessive autoinflammatory disorder. This study aimed to compare the clinical and laboratory profiles of FMF patients stratified by their MEFV genotype into three groups: simple heterozygotes, compound heterozygotes, and homozygotes. OBJECTIVES: To evaluate the association between MEFV gene mutations and clinical features, acute phase reactants, and hematological parameters in patients with FMF in Nineveh Province, Iraq. PATIENTS AND METHODS: This retrospective cohort study included 60 FMF patients from Nineveh Province, Iraq. Diagnosis was based on both Tel Hashomer and Livneh criteria. Genetic analysis targeted 12 common MEFV mutations. Patients were re-classified into three genetic groups for analysis. RESULTS: Among the 60 patients, 25 (41.7%) were simple heterozygotes, 20 (33.3%) were compound heterozygotes, and 15 (25.0%) were homozygotes. The most frequent mutations were M694V and M694I. Abdominal pain and fever were the most prevalent symptoms, with homozygotes showing the highest frequency. Homozygous patients exhibited significantly higher levels of erythrocyte sedimentation rate, C-reactive protein, neutrophils, and lymphocytes compared to the other groups. Proteinuria was also most frequent in the homozygous group (86.7%). CONCLUSIONS: Genetic stratification reveals a clear gradient in clinical and inflammatory severity. Homozygous mutations are associated with a more severe phenotype, including higher inflammatory markers and more frequent proteinuria, followed by compound heterozygotes. These findings underscore the critical importance of detailed genetic profiling for risk stratification and management in FMF.